Cost Calculation as an Operationalization of Management Accounting: Opinions, Options and Realities - Ciuhureanu Alina Teodora (Scientific Bulletin, 2023)
Managers need accurate and timely information to carry out pricing, planning, operational exploitation and other types of decisions. Regardless of the level at which he is, the manager manages his area of responsibility, triggers actions that will lead to the realization of effects, only through the consumption of resources. Knowledge and analysis of costs is a fundamental step in establishing an optimal price policy leading to the achievement of the objectives. From this perspective, the paper addresses the importance of cost knowledge and prices calculation methods in terms of managerial advantages and disadvantages. Also, based on a research conducted on a sample of 301 organizations, we aimed to reach the objective of knowing the options regarding cost calculation as operationalization of the capitalization of the information provided through management accounting.